(untitled) (Entrepreneurship Journal for Finance and Business, 2023)
Desertification is not a modern phenomenon, but the seriousness of this phenomenon has exacerbated and increased in recent times, and the problem of desertification has become a global problem, and it is basically a man-made phenomenon that is exacerbated by climate changes. Soil erosion, erosion, spread of sand dunes, land degradation, low crop productivity, weak capacity of agricultural and pastoral systems, and many social problems. Therefore, it is at the heart of the serious challenges and threats facing sustainable development with far-reaching negative effects on natural resources, the environment, economic and agricultural activity, physical infrastructure, and food security. The research problem is The continuous rise in the ever-increasing and changing human requirements of agricultural and food commodities and the increase in population and the consequent social changes have doubled the need to exploit additional resources to meet food requirements at a time when large areas of land suffer from the problem of desertification, The research aims to know the reasons for the exacerbation of the phenomenon of desertification and its repercussions on the agricultural sector in Iraq, The consequences thereof and the possibilities available for treatment. We assume that human factors exert the strongest influence in the exacerbation of this phenomenon to side Unsustainable Exploitation of Natural Resources The research concluded that desertification is one of the environmental problems that the more they aggravate and increase in severity, The more difficult and costly it will be to treat them financially and technically.